Sowing The Construction of Historical Longitudinal Population Databases - Mandemakers, Kees (Radboud University Press, 2023)
Twenty-three major databases containing historical longitudinal population data are presented and discussed in this volume, focusing on their aims, content, design, and structure. Some of these databases are based on pure longitudinal sources, such as population registers that continuously observe and record demographic events, including migration and family and household composition. Other databases are family reconstitutions, based on birth, marriage and death records. The third and last category consists of semi-longitudinal databases, that combine, for instance, civil records and censuses and/ or tax registers. The volume traces the origins of historical longitudinal databases from the 1970s and discusses their expansion worldwide, in terms of sources and hard- and software. The contributions highlight the unique genesis and common developmental arcs of these databases, which are rooted in the fields of quantitative history, social and demographic history, and the history of ordinary people. The importance of these databases in advancing knowledge and insights in various disciplines is emphasized and demonstrated, along with the challenges and opportunities they face. The collection of technical descriptions of these databases represents the most comprehensive and up-to-date overview of large database with longitudinal micro-data on historical populations. It includes descriptions of databases from Europe, North America, East-Asia, Australia, South-Africa and Suriname. Technical details, in terms of data entry, cleaning, standardization and record linkage are meticulously documented. The volume is a must-have for all scholars in the field of historical life course studies.